Characterization of DtrJ as an IncC plasmid conjugative DNA transfer component. Issue 1 (24th February 2021) - Hancock, Steven J.; Phan, Minh‐Duy; Roberts, Leah W.; Vu, Thu Ngoc Minh; Harris, Patrick N. A.; Beatson, Scott A.; Schembri, Mark A.
Abstract: Incompatibility group C (IncC) plasmids are large (50–400 kb), broad host range plasmids that drive the spread of genes conferring resistance to all classes of antibiotics, most notably the bla NDM gene that confers resistance to last‐line carbapenems and the mcr‐3 gene that confers resistance to colistin. Several recent studies have improved our understanding of the basic biological mechanisms driving the success of IncC, in particular the identification of multiple novel IncC conjugation genes by transposon directed insertion‐site sequencing. Here, one of these genes, dtrJ, was examined in further detail. The dtrJ gene is located in the DNA transfer locus on the IncC backbone, and quantitative reverse‐transcriptase PCR analysis revealed it is transcribed in the same operon as the DNA transfer genes traI and traD (encoding the relaxase and coupling protein, respectively) and activated by the AcaDC regulatory complex. We confirmed that DtrJ is not required for pilus biogenesis or mate pair formation. Instead, DtrJ localizes to the membrane, where it interacts with the coupling protein TraD and functions as an IncC DNA transfer protein. Overall, this work has defined the role of DtrJ in DNA transfer of IncC plasmids during conjugation. Abstract : This manuscript describes the function of the conjugation protein, DtrJ. We show that DtrJ is critical for the DNA transfer step of plasmid conjugation and may be involved in specific DNA substrate selection during conjugation.